Rye-wheat bread production with the use of the accelerated technologies at the restaurant establishments - Sylchuk, Tetiana; Kovalenko, Anna (My University, 2013)
The technological process of dough-making of rye flour on accelerated technology with using of "Ibis" integrated (complex) bakery improvers is investigated. The Influence of "Ibis" improvers on the process of accumulation of acids, structural and mechanical properties of dough and quality of bread is analysed.
Keywords: rye flour; bread; enzymatic additives; ржаная мука; хлеб; ферментные препараты; житнє борошно; хліб; ферментні препарати; кафедра готельно-ресторанної справи